2011
DOI: 10.1017/s1368980010003423
|View full text |Cite
|
Sign up to set email alerts
|

Donated breast milk substitutes and incidence of diarrhoea among infants and young children after the May 2006 earthquake in Yogyakarta and Central Java

Abstract: Objective: Distribution of breast milk substitutes (BMS) after the 2006 Yogyakarta earthquake was uncontrolled and widespread. We assessed the magnitude of BMS distribution after the earthquake, its impact on feeding practices and the association between consumption of infant formula and diarrhoea among infants and young children. Design: One month after the earthquake, caregivers of 831 children aged 0-23 months were surveyed regarding receipt of unsolicited donations of BMS, and on recent child-feeding pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 16 publications
0
55
0
6
Order By: Relevance
“…The widespread and unscreened distribution of infant formula have been documented across a number of emergency situations, including the Tsunami 2004 in India (Adhisivam et al . 2006), the Central Java earthquake in 2006 (Hipgrave et al . 2011), the Philippines typhoon in 2007 (Anonymous 2007), the China earthquake in 2008 (Bengin et al .…”
Section: Introductionmentioning
confidence: 99%
“…The widespread and unscreened distribution of infant formula have been documented across a number of emergency situations, including the Tsunami 2004 in India (Adhisivam et al . 2006), the Central Java earthquake in 2006 (Hipgrave et al . 2011), the Philippines typhoon in 2007 (Anonymous 2007), the China earthquake in 2008 (Bengin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Both the Jogjakarta earthquake and the Sichuan earthquakes were the subject of UNICEF reports (UNICEF 2010;Hipgrave, Assefa et al 2011). However while the Jogjakarta report emphasized infants and the adverse effects of infant formula distribution, the China report makes no mention of infant formula distribution and its effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, after the earthquake in Yogyakarta, Indonesia in 2006, a study found that rates of diarrhoea doubled among infants who had been given donated infant formula compared with those who had not [6]. During the floods in Botswana in 2006, infants hospitalised with diarrhoea were 30 times more likely not to be breastfed compared with infants without diarrhoea [7].…”
Section: Introductionmentioning
confidence: 99%